2021
DOI: 10.1186/s40729-021-00298-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the sinus membrane thickness in edentulous regions: a cone-beam computed tomography study

Abstract: Background During implant treatment in the maxillary molar area, maxillary sinus floor augmentation is often performed to ameliorate the reduced alveolar bone height attributable to bone remodeling and pneumatization-induced expansion of the maxillary sinus. However, this augmentation may cause complications such as misplaced implants, artery damage, and maxillary sinus mucosal perforation; infections like maxillary sinusitis; and postsurgical complications such as bone graft leakage and postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Ongoing discussion exists on a standard imaging threshold for the maxillary sinus mucosal thickness. With most studies using 1 mm as a standard [ 50 , 51 ], we simplified the maxillary sinus membrane by setting its thickness to 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing discussion exists on a standard imaging threshold for the maxillary sinus mucosal thickness. With most studies using 1 mm as a standard [ 50 , 51 ], we simplified the maxillary sinus membrane by setting its thickness to 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is most common to see sinus membrane thickening even in patients who are clinically asymptomatic and it is concluded that sinus membrane thickness of more than 4 mm is pathological in nature [ 16 ]. It is highly essential for the clinician to correlate the radiographic and clinical findings and plan the treatment accordingly [ 17 ]. The cause of the sinus membrane thickening and fluid accumulation may be due to "Acute rhinosinusitis" if the symptoms such as posterior or anterior nasal discharge, blockage of nose, congestion develops within 12 weeks of time duration [ 18 ] .Radiographic imaging reveals changes in the mucosa with hazy, fluid filled ostiomeatal complex.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our previous study [ 13 ], the presence of NSD was determined on coronal CBCT by the method described by Bhandary and Kamath [ 14 ]. A straight line was drawn from the maxillary anterior spine to the crista galli.…”
Section: Methodsmentioning
confidence: 99%